PRAKTEK BOLI PADA MASYARAKAT BATAK MANDAILING DAN RELEVANSINYA DENGAN KEHARMONISAN RUMAH TANGGA PERSPEKTIF KOMPILASI HUKUM ISALM (KHI) - Hasibuan, Saparuddin (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2024)
This study discusses the practice of boli in the Batak Mandailing community and its relevance to household harmony from the perspective of the Compilation of Islamic Law (KHI). The problem in this study is about the practice of boli, which is to marry a woman who is pregnant out of wedlock with another man who is not impregnated with her by giving payment or rewards in the form of money, land, work gardens or others, and all wedding costs are fully borne by the woman's family. The purpose of this study is to discuss the implementation of boli practices in the Batak Mandailing community, discuss the harmony of boli households, and analyze the Compilation of Islamic Law on boli practices. The research method used is field research (file research), which starts from data collection: observation, interviews, documentation, both primary: actors and community leaders and secondary: literature and from community leaders who know related issues. The data will be traced in literature that is considered relevant. The results of the study show that the implementation of the practice of boli is carried out by looking for a man who wants to marry his daughter who is pregnant out of wedlock by giving a reward in the form of money. The harmony of the household of the boli perpetrator from the interview with the author of all the household actors still survives or lasts. The analysis of the synthesis of Islamic law in the practice of boli is that in article 53 it is stated that marriage with a pregnant woman outside of wedlock can only be married to the man who impregnates. If the one who marries her is another man who is not impregnating her, then her marriage is marriage sirri.